2022
DOI: 10.1002/bmc.5525
|View full text |Cite
|
Sign up to set email alerts
|

Effects of voriconazole and fluconazole on the pharmacokinetics of almonertinib in rats by UPLC–MS/MS

Abstract: Almonertinib was included in the first‐line treatment of non‐small cell lung cancer with EGFR T790M mutations by the Chinese Society of Clinical Oncology in 2021. Considering that immunocompromised lung cancer patients are prone to opportunistic fungal infections, and most triazole antifungal drugs are moderate or strong inhibitors of CYP3A4, this study was conducted to develop and validate an accurate and rapid ultra‐performance liquid chromatography tandem mass spectrometry method for quantifying almonertini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…It has been reported that CYP3A4 is the main enzyme system responsible for catalyzing the generation of HAS-719 from aumolertinib. Due to its rich genetic polymorphism and susceptibility to drug induction or inhibition, changes in CYP3A4 enzyme activity can lead to fluctuations in aumolertinib blood exposure and affect efficacy (Zhou, 2008;Fu et al, 2023). Although other factors, such as food, gender, age, and more, can also influence the pharmacokinetic characteristics of drug metabolism, these aspects were not the focus or within the scope of the present study (Hoover et al, 2016).…”
Section: Frontiers In Pharmacology Frontiersinorg 10 4 Discussionmentioning
confidence: 94%
“…It has been reported that CYP3A4 is the main enzyme system responsible for catalyzing the generation of HAS-719 from aumolertinib. Due to its rich genetic polymorphism and susceptibility to drug induction or inhibition, changes in CYP3A4 enzyme activity can lead to fluctuations in aumolertinib blood exposure and affect efficacy (Zhou, 2008;Fu et al, 2023). Although other factors, such as food, gender, age, and more, can also influence the pharmacokinetic characteristics of drug metabolism, these aspects were not the focus or within the scope of the present study (Hoover et al, 2016).…”
Section: Frontiers In Pharmacology Frontiersinorg 10 4 Discussionmentioning
confidence: 94%
“…Xun et al revealed that VCZ inhibited the metabolism of atorvastatin, and had a significant interaction with atorvastatin in patients with fungal infections and dyslipidemia ( Xun et al, 2023 ). A recent study demonstrated that VCZ and FCZ increased the systemic exposure of almonertinib by 2.7-fold and 3.4-fold, respectively ( Fu et al, 2023 ). Midazolam is regularly utilized as a probe substrate to assess CYP3A activity, and the AUC 0–360 of midazolam was significantly increased (133%) ( U.S. Food and Drug Administration, 2017 ; European Medicines Agency, 2012 ; Uchida, Tanaka & Namiki, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The validation process encompassed the assessment of various parameters, such as selectivity, calibration curve, lower line of quantification (LLOQ), accuracy, precision, matrix effect, recovery and stability. 21…”
Section: Methods Validationmentioning
confidence: 99%
“…This study was validated conducted in accordance with the bioanalytical method validation principles established by FDA. The validation process encompassed the assessment of various parameters, such as selectivity, calibration curve, lower line of quantification (LLOQ), accuracy, precision, matrix effect, recovery and stability 21 …”
Section: Methodsmentioning
confidence: 99%